EFFECT OF NANOSILICA FROM RICE HUSK ON THE GROWTH ENHANCEMENT OF CHILI PLANT (Capsicum frutescens L.) - Dung, Pham Dinh; Ngoc, Le Si; Duy, Nguyen Ngoc; Thuy, Nguyen Ngoc; Truc, Lu T. Minh; Le, Bui Van; Phu, Dang Van; Hien, Nguyen Quoc (Vietnam Journal of Science and Technology, 2016)
Nanomaterials hold great promise of improved plant disease resistance, controlled release of agro-chemicals, enhanced plant growth, etc. In this study, the effect of nanosilica (10 – 30 nm) prepared from rice husk on the growth promotion of chili plant in green house was carried out. The experiment of nanosilica treatment by foliar spraying was arranged in a factorial design with 3 replications at various nanosilica concentrations of 0, 40, 60 and 100 ppm. Plant growth characteristics and chlorophyll content were assessed. Results showed that the fresh weight, dry weight, and chlorophyll content increased with the treatment of nanosilica. The optimal concentration of nanosilica was found to be of 60 ppm. Thus, treatment of nanosilica was beneficial in enhancing the growth of the chili plants.